PEMBELAJARAN YOGA DALAM PEMBENTUKAN KARAKTER SISWA DI PASRAMAN SAMIAGA MATARAM - Windariyanti Windariyanti; I Nyoman Wijana; Ni Putu Listiawati (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Pasraman is a Hindu education system which aims to give birth to the younger generation who is not only a candidate in religious knowledge, but also has a noble character. One of the learning held by most of the pasraman is yoga learning as an effort to raise awareness of health and form of students character. Referring to that background, the writer conducted a study related to yoga learning that focused on planning, implementing, evaluating, and characters formed through yoga learning at Pasraman Samiaga Mataram. This research was conducted using qualitative methods with descriptive qualitative data analysis. Data obtained from observation, interview, documentation, and checking data validity carried out with credibility, transferability, dependability, and confirmability. This research supported by behavioristic theory, Burner learning theory and theory of learning connectionism. This study shown that yoga learning planning carried out by instructor by determining the learning objectives, designing learning materials, and determine the learning schedule. In the implementation of yoga learning is done gradually and at each stage tugged the strengthening of the character for the students. As for the stages of yoga learning at Pasraman Samiaga Mataram includes preparation stage, appetite prayer, stretching, surya namaskara, asanas, acro yoga, relaxation, and prayer cover. The evaluation of yoga learning which is carried out includes evaluation of process and evaluation of results are overseeing the development of each student’s ability, carry out assessment at each meeting, and held a yoga race in the pasraman. The characters formed through yoga learning at Pasraman Samiaga Mataram includes religious character, discipline character, the characters are responsible, character appreciate achievement, character of curiosity and independent character.